Water circulation pattern of Port Dickson in August 1988. - Saadon, M. N.; Liew, Hee Chong (1990)
The study was conducted in front of the UPM Station in Port Dickson between 21st August to 25th August 1988. Two methods were used in this study, i.e. the Lagrangian and Eulerian methods. In the Lagrangian method two drogues were used. They were deployed at 2m and 3m depth. In this study it was found that both drogues tend to move southward and towards the beach. In the Eulerian method a self-recording current meter was used and deployed at 2m depth. Data of current speed and direction were recorded and analysed using scattered plot diagrams, stick diagrams and progressive vector plots. In general, the currents flow in a predominantly north-south direction. However in the progressive vector plots the southward direction was found to be more dominant. The current speed was in the range of 0 - 0.35 m/s. This information on water circulation helped in tracking the possible movement of pollutants from Port Dickson to Teluk Kemang beach.